Performance of quality improvement offices in hospitals: Challenges and Approaches - Ebrahim Jaafari pooyan (Tehran University of Medical Sciences, 2020)
Introduction: Identifying the challenges of Quality Improvement Offices (QIOs) not only helps in planning the quality of hospital services and in trying to provide a suitable solution to solve the problems of these offices but also plays an important role in strengthening the offices and increasing the quality of clinical and non-clinical services of hospitals. This study aimed to investigate the challenges of quality improvement offices in hospitals and provide appropriate solutions. Methods: The present qualitative research was conducted using semi-structured interviews with 40 managers and hospital boards, matrons, quality improvement experts of hospitals and accreditation offices experts of medical universities in Tehran. Content analysis method was used to analyze the data obtained from the interviews. Then, the collected data were analyzed and classified by MAXQDA10 software. Results: By analyzing the interviews in the field of challenges and solutions, the extracted codes were classified into four areas of management, standards, evaluation and staff. The most codes were related to management with 5 themes and 21 sub-themes. In addition, most of the solutions were related to the field of management. Conclusion: The findings of the study showed that most of the challenges and solutions were in the field of management. Focusing on this field could be helpful in improving the quality of offices performance.